The Pattern of Employment in Nigeria between 1981 and 2014 - Adeniyi, Adetunji (International Journal of Learning and Development, 2024)
Unemployment is a major macroeconomic malaise in Nigeria. It has been high and rising over the years across dictatorship, democratic, administrative, and economic regimes. In the process sectoral employment transitioned from the productive sectors of agriculture and manufacturing to services sectors of trade and services and administration sectors of the economy. This study examined the patterns of unemployment and the transitioning of sectoral employment during the economic growth period between 1981 and 2014. It concluded that, despite the fact that economic growth was a common factor, unemployment worsened during democracy, and more so under the Yar’Adua / Jonathan administration. Unemployment was best managed under the military, ironically, and better under the Obasanjo administration, respectively.